Hubungan Persepsi Kerentanan, Persepsi Hambatan Dan Dukungan Sosial Dengan Kepatuhan Latihan Fisik Pada Lansia Hipertensi - Trisno Putri, Noor Rochmah Ida Ayu; Rekawati, Etty; Wati, Dwi Nurviandari Kusuma (Universitas Harapan Bangsa, 2025)
Hypertension, a chronic condition often experienced by the elderly and can cause serious complications if not managed properly. Physical exercise is an important non-pharmacological strategy to control blood pressure, however, the level of elderly compliance with exercise is still low. This study analyzed the relationship between perceived vulnerability and perceived barriers with physical exercise compliance in 108 elderly with hypertension in the Tugu Community Health Center (Puskesmas) work area, Depok. Data were collected using a questionnaire based on the Health Belief Model (HBM), and analyzed using the chi-square test and multiple logistic regression. The results showed that 55.6% of elderly had low compliance with physical exercise. Bivariate analysis showed a significant relationship between compliance with perceived vulnerability (p=0.018; OR=2.77) and perceived barriers (p=0.004; OR=2.39). Multiple logistic regression confirmed that elderly with high perceived vulnerability were 3.12 times more adherent, while those with fewer perceived barriers were 3.05 times more adherent. The dominant factor was social support (OR=3.60). Perceived vulnerability and perceived barriers play an important role in physical exercise compliance in elderly with hypertension. Improving health education to raise risk awareness and reducing barriers through targeted interventions, family involvement, and community support are important strategies. These findings underscore the need to integrate psychosocial factors into geriatric community nursing to improve hypertension management in older adults.